2010
DOI: 10.4317/medoral.15.e467
|View full text |Cite
|
Sign up to set email alerts
|

Screening for hypertension in a primary care dental clinic

Abstract: Objective: The aim of this study was to record blood pressure in patients during their visit to a dental clinic, with the aim of identifying those who have high blood pressure and are unaware of it, as well as those who are aware of their condition but do have their blood pressure under adequate control. Study design: We designed a cross-sectional study which included 154 patients who were seen for a dental checkup at the Primary Dental Care of the Gallician Health Service (SERGAS). All participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
(9 reference statements)
1
16
0
4
Order By: Relevance
“…A study conducted in Nigeria reported hypertension in approximately 20% of dental patients; half of these cases were undiagnosed until they were examined at the dental clinic [3]. Similarly, in another study, approximately 29% of patients were reported to have hypertension when examined in a dental clinic; 73% of these patients were referred to a family physician because they were unaware of their medical condition [4]. Therefore, it seems that dentists may play a crucial role in diagnosing this silent killer disease.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Nigeria reported hypertension in approximately 20% of dental patients; half of these cases were undiagnosed until they were examined at the dental clinic [3]. Similarly, in another study, approximately 29% of patients were reported to have hypertension when examined in a dental clinic; 73% of these patients were referred to a family physician because they were unaware of their medical condition [4]. Therefore, it seems that dentists may play a crucial role in diagnosing this silent killer disease.…”
Section: Introductionmentioning
confidence: 99%
“…Esse procedimento pode contribuir no reconhecimento da doença e na consequente intervenção precoce, bem como no tratamento correto dos pacientes através de reforço e estímulo para adesão à terapia, seja esta medicamentosa ou não. Além disso, o monitoramento da pressão arterial deve ser realizado necessariamente naqueles pacientes que sabidamente possuem algum comprometimento de saúde 16,17,24,32 .…”
Section: Discussionunclassified
“…Recentemente, tem sido proposto o rastreamento (screening) para a hipertensão arterial durante as visitas odontológicas [14][15][16][17] . Uma grande parcela da população em geral frequenta regularmente um consultório odontológico, seja este público ou privado.…”
Section: Introductionunclassified
See 2 more Smart Citations